Quantitative Paraspinal Muscle Measurements: Inter-Software Reliability and Agreement Using OsiriX and ImageJ. - Fortin, Maryse; Battié, Michele C. (Physical Therapy, 2012)
Background. Variations in paraspinal muscle cross-sectional area (CSA) and composition, particularly of the multifidus muscle, have been of interest with respect to risk of, and recovery from, low back pain problems. Several investigators have reported on the reliability of such muscle measurements using various protocols and image analysis programs. However, there is no standard protocol for tissue segmentation, nor has there been an investigation of reliability or agreement of measurements using different software. Objective. The purpose of this study was to provide a detailed muscle measurement protocol and determine the reliability and agreement of associated paraspinal muscle composition measurements obtained with 2 commonly used image analysis programs: OsiriX and ImageJ. Design. This was a measurement reliability study. Methods. Lumbar magnetic resonance images of 30 individuals were randomly selected from a cohort of patients with various low back conditions. Muscle CSA and composition measurements were acquired from axial T2-weighted magnetic resonance images of the multifidus muscle, the erector spinae muscle, and the 2 muscles combined at L4-L5 and S1 for each participant. All measurements were repeated twice using each software program, at least 5 days apart. The assessor was blinded to all earlier measurements. Results. The intrarater reliability and standard error of measurement (SEM) were comparable for most measurements obtained using OsiriX or ImageJ, with reliability coefficients (intraclass correlation coefficients [ICCs]) varying between .77 and .99 for OsiriX and .78 and .99 for ImageJ. There was similarly excellent agreement between muscle composition measurements using the 2 software applications (intersoftware ICCs=.81-.99). Limitations. The high degree of inter-software measurement reliability may not generalize to protocols using other commercial or custom-made software. Conclusion. The proposed method to investigate paraspinal muscle CSA, composition, and side-to-side asymmetry was highly reliable, with excellent agreement between the 2 software programs.